Outcome after kidney transplantation in hepatitis B surface antigen-positive patients - Hyejin Mo; Sangil Min; Ahram Han; In Mok Jung; Jongwon Ha (Scientific Reports, 2021)
Abstract Few reports detail the actual outcome of Hepatitis B Surface Antigen-positive patients after kidney transplant. HBsAg-positive patients who underwent kidney transplant between January, 1999, and December, 2018, were reviewed retrospectively. Outcomes including hepatitis B reactivation rate, risk factors for reactivation, and patient and graft survival rates were analyzed. Seventy-seven patients were enrolled (47.1 ± 11.5 years old). Patients received ABO-incompatible (n = 5), crossmatch positive transplant (n = 2), and re-transplant (n = 4). Forty-six patients received prophylactic; 19, medication at least 3 months before the transplant; and 12, did not receive medication. Seventeen out of 76 patients developed reactivation post-transplant. 52.9% of HBV reactivation was accompanied by hepatitis. Inappropriate, other than lifelong prophylactic, antiviral agents (HR = 7.34, 95% CI 1.51–35.69, P = 0.01) and high hepatitis DNA (≥ 1000 IU/ml) pre-transplant (HR = 4.39, 95% CI 1.08–17.81, P = 0.04) increased reactivation risk. There was no significant difference in patient and graft survival between antigen positive patients who received antiviral agent and propensity score matched negative patients. HBsAg positivity in kidney transplant recipients is associated with substantial HBV reactivation rate. Lifelong antiviral therapy is mandatory, and patients with high preop HBV titer should be monitored closely for HBV reactivation.